Green synthesis and characterization of copper-based nanoparticles using fruit peel exrtracts from selected Philippine citrus species - Anjela Nicole M. Aguinaldo, Nathaniel John A. Basig, Michaella Nicole M. Laberinto, Seane Ivoree F. Leviste, Rene A. Tahil, Jr. 4 0 16; 5 (2023)
u
Undergraduate Thesis: (Bachelor of Science in Chemistry) Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2